2012
DOI: 10.2741/3974
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial and nuclear genomic integrity after oxidative damage in Saccharomyces cerevisiae

Abstract: All cells have the ability to adjust their metabolism to their changing environment to be able to survive. This adaptation is coordinated by various systems in the cell and mitochondria seem to play a unique and important role. Most endogenous oxidative damage to cells is actually generated as a byproduct of the mitochondrial function, which in turn damages mitochondrial structures more extensively due to their proximity to the source. Excessive damage to mitochondria leads to loss of parts or all of mtDNA, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 108 publications
2
14
0
Order By: Relevance
“…The leakage of electrons from the mitochondrial respiratory chain is pointed out as the main source of endogenous ROS in S. cerevisiae. However, S. cerevisiae is known to tolerate the loss of mtDNA (Yazgan and Krebs 2012), which makes this organism a useful model to evaluate how the mitochondrial respiratory chain is involved in Pb-induced oxidative stress. Thus, to evaluate whether mitochondrial function was the source of Pb-induced oxidative stress and, consequently, was associated with Pb toxicity, cells from an RD ρ 0 strain (lacking mtDNA) were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leakage of electrons from the mitochondrial respiratory chain is pointed out as the main source of endogenous ROS in S. cerevisiae. However, S. cerevisiae is known to tolerate the loss of mtDNA (Yazgan and Krebs 2012), which makes this organism a useful model to evaluate how the mitochondrial respiratory chain is involved in Pb-induced oxidative stress. Thus, to evaluate whether mitochondrial function was the source of Pb-induced oxidative stress and, consequently, was associated with Pb toxicity, cells from an RD ρ 0 strain (lacking mtDNA) were used.…”
Section: Discussionmentioning
confidence: 99%
“…This inability to grow on glycerol can be used as a measure of the partial or complete loss of mtDNA (Yazgan and Krebs 2012).…”
Section: Pb-induced Production Of Superoxide Anion and Hydrogen Peroxidementioning
confidence: 99%
“…ROS accumulation due to mitochondrial disorder causes destabilization of the mitochondrial and/or nuclear genome. (35,36) BE and its polyphenols effectively suppressed AAPH-induced ROS accumulation in not only cytoplasm but also nuclear (Fig. 4).…”
Section: Discussionmentioning
confidence: 85%
“…(33,34) We previously reported that BE and its component procyanidins and C3G enhanced protein expression of GST family in HepG2 cells. (35) Thus, prevention effect of BE and its polyphenols against ROS accumulation were two ways: a direct radical scavenging activity and inducing GSTs expression indirectly. ROS accumulation due to mitochondrial disorder causes destabilization of the mitochondrial and/or nuclear genome.…”
Section: Discussionmentioning
confidence: 99%
“…RD cells are unable to grow on nonfermentable carbon sources, such as glycerol. 55 In a previous work, it was found that the mitochondrion is the main source of intracellular ROS induced by NiO NPs. 19 Because mtDNA is very susceptible to oxidative injury, 56 the possibility of the mitochondrial genome being damaged upon exposure to NiO was evaluated by determining the percentage of RD cells.…”
Section: Impact Of Nio Nps On Cell Viability and Plasmamentioning
confidence: 98%